Transcriptome and weighted gene co-expression network analysis of jujube (Ziziphus jujuba Mill.) fruit reveal putative genes involved in proanthocyanin biosynthesis and regulation - Wenqiang Wang; Yunfeng Pu; Hao Wen; Dengyang Lu; Min Yan; Minzhe Liu; Minyu Wu; Hongjin Bai; Lirong Shen; Cuiyun Wu (Food Science and Human Wellness)
Proanthocyanidin (PA) is an important bioactive compound with multiple physiological benefits in jujube (Ziziphus jujube Mill.). However, the molecular mechanisms underlying PA biosynthesis in jujube fruit have not been investigated. Here, the profiling of PA, (+)-catechin and (–)-epicatechin and transcriptome sequencing of three jujube cultivars from Xinjiang Uyghur Autonomous Region of China at five developmental stages were analyzed. The levels of total PAs and catechin exhibited a decreased trend over jujube ripening, and epicatechin content of two jujube cultivars increased first and then declined. Transcriptome analysis revealed that the differentially expressed genes (DEGs) were mainly enriched in ribosome, glycolysis/gluconeogenesis, fructose and mannose metabolism. 17 DEGs encoding PAL, CHS, CHI, CHS, F3’H, LAR, ANR, C4Hs, 4CLs, FLSs, DFRs and UFGTs involved in PA biosynthesis were relatively abundant. The highly transcribed LAR gene may greatly contribute to epicatechin accumulation. A weighted gene co-expression network analysis (WGCNA) was performed, and a network module including 1620 genes highly correlated with content of Pas and catechin was established. We identified 58 genes including 9 structural genes and 49 regulatory genes related to PA biosynthesis and regulation in the WGCNA module. Sixteen genes encoding 9 families of transcriptional factors (i.e., MYB, bHLH, ERF, bZIP, NAC, SBP, MIKC, HB, WRKY) were considered as hub genes. The results of qRT-PCR analysis validating 10 genes were well consistent with the transcriptome data. These findings provide valuable knowledge to facilitate its genetic studies and molecular breeding.